A complete assessment of tagging quality: A consolidated methodology - Choi, Yunseon (Association for Information Science and Technology, 2015)
This paper presents a methodological discussion of a study of tagging quality in subject indexing. The data analysis in the study was divided into 3 phases: analysis of indexing consistency, analysis of tagging effectiveness, and analysis of the semantic values of tags. To analyze indexing consistency, this study employed the vector space model-based indexing consistency measures. An analysis of tagging effectiveness with tagging exhaustivity and tag specificity was conducted to ameliorate the drawbacks of consistency analysis based on only the quantitative measures of vocabulary matching. To further investigate the semantic values of tags at various levels of specificity, a latent semantic analysis (LSA) was conducted. To test statistical significance for the relation between tag specificity and semantic quality, correlation analysis was conducted. This research demonstrates the potential of tags for web document indexing with a complete assessment of tagging quality and provides a basis for further study of the strengths and limitations of tagging.
3 citations (Crossref) [2023-10-31] tex.type: Proceedings paper Citation Key Alias: ISI:000351395800010
Keywords: Consistency analysis; Consistency measures; Correlation analysis; Indexing (of information); Information retrieval; Latent Semantic Analysis; Organization of informations; Quality control; Quantitative measures; Semantics; Statistical significance; Subject indexing; Vector spaces; clinical trial; correlation analysis; data analysis; dept.ils; human; information retrieval; linguistics; model; organization of information; quantitative study; statistical significance; subject indexing

Analyzing tagging patterns by integrating visual analytics with the inferential test - Choi, Yunseon (ACM/IEEE Joint Conference on Digital Libraries, 2015)
Due to the large volume and complexity of data, exploring data using visual analytics has become more helpful to interpret and analyze it. The box plot is one of graphical ways and is the most common technique for presenting and summarizing statistics. In this paper, we focus on discussing the tagging patterns by integrating visualization assessment using the box plot with the Shapiro-Wilk test. © 2015 Author.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Data analytics; Data visualization; Digital libraries; Large volumes; Shapiro-Wilk tests; Social tagging; Visual analytics; Visualization; data analytics; data visualization; dept.ils; social tagging

Content analysis of social tags generated by health consumers - Joo, Soohyung; Choi, Yunseon (ACM/IEEE Joint Conference on Digital Libraries, 2015)
This poster presents preliminary findings of user tag analysis in the domain of consumer health information. To obtain user terms, 36,205 tags from 38 consumer health information sites were collected from delicious.com. Content analysis was applied to identify the dimensions and types of the collected tags. The preliminary findings showed that user generated tags covers a variety of aspects of health information, ranging from general terms, subject terms, knowledge type, and to audience. General terms and subject terms were observed dominantly by showing 31.7% and 22.8% respectively. © 2015 Authors.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Consumer health information; Content analysis; Digital libraries; Health; Health informations; Knowledge types; Qualitative analysis; Social Tags; Social networking (online); Social tagging; User-generated; consumer health information; dept.ils; qualitative analysis; social tagging

A library in the palm of your hand: mobile services in top 100 university libraries - Liu, Yan Quan; Briggs, Sarah (Information Technology and Libraries, 2015)
What is the current state of mobile services among academic libraries of the country's top 100 universities, and what are the best practices for librarians implementing mobile services at the university level? Through in-depth website visits and survey questionnaires, the authors studied each of the top 100 universities' libraries' experiences with mobile services. Results showed that all of these libraries offered at least one mobile service, and the majority offered multiple services. The most common mobile services offered were mobile sites, text messaging services, e-books, and mobile access to databases and the catalog. In addition, chat/IM services, social media accounts and apps were very popular. Survey responses also indicated a trend towards responsive design for websites so that patrons can access the library's full site on any mobile device. Respondents recommend that libraries considering offering mobile services begin as soon as possible as patron demand for these services is expected to increase.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-328-507-257-353 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils; peer-reviewed